MANAGEMENT OF INFORMATION SUPPORT FOR FINANCIAL SECURITY OF ENTERPRISES - KRYMCHAK, Liudmyla; SLOBODYANYUK, Ivanna; KRYMCHAK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of information support as a key element of effective enterprise management and a guarantee of its financial security. The paper reveals the essence of information support, analyzes the structure of information resources, identifies the stages of development of modern information systems, and highlights the principles on which their functioning should be based. The main stages of forming information support for innovative activities include: implementation of basic information systems, optimization and expansion of the functionality of information support, integration and efficiency improvement. Particular attention is paid to the role of analytical information and system adaptability. It is determined that supporting continuous information exchange is one of the most important elements of information support in modern companies. The paper presents the main levels of information support for the financial security of the enterprise: administrative, procedural and technical. The basis of measures carried out at each of these levels is also determined. Such measures include: control of publications about the activities of the enterprise, prevention of complaints, observance of personnel discipline in terms of commercial secrets, certification, accreditation, information assessment, risk assessment, security planning, information support, legal support, software support, etc. The presented materials of the article allow a deeper understanding of the importance of high-quality information flow in the conditions of the modern changing environment and can be useful for many specialists in the field of management, economics and IT.
Keywords: information; information support; information resource; information analysis; information support of financial security